2015
DOI: 10.1111/anu.12301
|View full text |Cite
|
Sign up to set email alerts
|

Influence of one selectedTisochrysis luteastrain rich in lipids onCrassostrea gigaslarval development and biochemical composition

Abstract: Effects of a remarkably high overall lipid Tisochrysis lutea strain (T+) upon gross biochemical composition, fatty acid (FA), sterol and lipid class composition of Crassostrea gigas larvae were evaluated and compared with a normal strain of Tisochrysis lutea (T) and the diatom Chaetoceros neogracile (Cg). In a first experiment, the influence of different single diets (T, T+ and Cg) and a bispecific diet (TCg) was studied, whereas, effects of monospecific diets (T and T+) and bispecific diets (TCg and T+Cg) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 95 publications
1
19
0
Order By: Relevance
“…At steady state of this experiment in chemostat, the mutant strain limited by nitrogen accumulates 2 to 3-fold more storage lipids than the WT strain and membrane lipid were quite similar. Alkenones were very low in the mutant strain as previously observed [92]. The 2.2fold down-accumulated in 2Xc1 of the Very-long-chain 3-oxoacyl-CoA, putatively involved in alkenone biosynthesis, could have led to the lower concentration detected.…”
Section: Xc1: a Plastic Strain That Accumulates Carbohydrates And Stsupporting
confidence: 71%
“…At steady state of this experiment in chemostat, the mutant strain limited by nitrogen accumulates 2 to 3-fold more storage lipids than the WT strain and membrane lipid were quite similar. Alkenones were very low in the mutant strain as previously observed [92]. The 2.2fold down-accumulated in 2Xc1 of the Very-long-chain 3-oxoacyl-CoA, putatively involved in alkenone biosynthesis, could have led to the lower concentration detected.…”
Section: Xc1: a Plastic Strain That Accumulates Carbohydrates And Stsupporting
confidence: 71%
“…Holbach et al (2017) demonstrated that aeration had detrimental effects in small-volume (5 L) systems. Conversely, flow-through systems (without aeration) appeared to be a promising technique, though only at lower densities (10 larvae/mL) than those (e.g., 300 larvae/mL) that were successfully tested for professional purposes in oysters (Da Costa et al 2016;Robert et al 2017). Holbach et al (2017) also demonstrated that coupling a flow-through system with aeration, which may allow for higher larval density, increased P. maximus larval mortality, which reinforces the adverse effects of the hydrodynamic forces generated by aeration on this species.…”
Section: Discussionmentioning
confidence: 99%
“…The system solvent used for the pre-run and run was composed of methyl acetate:isopropanol:chloroform:methanol:KCl aqueous solution of 0.25% (10:10:10:4:3.6, v:v:v:v:v). This method, routinely used and adapted to marine animal matrices (mainly bivalves) [37][38][39], allowed the separation of not only the different phospholipid classes present in these matrices, cardiolipin (CL), sphingomyelin (SM), lysophosphatidylcholine (LPC), phosphatidylcholine (PC), phosphatidylethanolamine (PE), phosphatidylserine (PS), and phosphatidylinositol (PI), but also some particular microalgae glycolipids such as monogalactosyldiacylglycerol (MGDG) and digalactosyldiacylglycerol (DGDG). However, two PL classes, present in the microalgae B. braunii, sulfoquinovosyldiacylglycerol (SQDG) and phosphatidylglycerol (PG), were co-eluted with PE (Fig.…”
Section: Tl Extraction Protocolmentioning
confidence: 99%